中學體育教師在素養導向體育課程設計歷程的理解與反思 Secondary School Physical Education Teachers' Understanding and Practical Reflection of Competence-Based Curriculum Design - 陳萩慈 Chiu-Tsu Chen; 掌慶維 Ching-Wei Chang; 李宏盈 Hung-Ying Lee (National Changhua University of Education, 2023)
十二年國民基本教育所欲培育的核心素養為各學科的重要依據，惟中學體育教師對素養導向課程概念常未能有效與其教學實踐有效連結。依此，本研究運用逆向式課程設計（backward design），採逆向發展的設計與課程校準，引導教師朝向情境化、脈絡化、整合式的學習經驗設計，協助體育教師建立素養導向課程的深入理解概念，作為後續支持中學體育教師專業發展與實踐之參考。本研究選取5位中學體育教師及1位體育師資培育教授為研究對象，組織4次實務社群會議。資料蒐集採半結構式訪談、參與觀察、持續比較和歸納分析資料。結果顯示：一、社群運作初期，教師感到教學與評量間的矛盾，評量仍著重於技能學習；二、社群運作中，教師將目標設定、學習評量以及學習內容來回校準，嘗試化解「既有現場教學經驗」與「探究學習」間的矛盾，但對於素養導向評量概念尚未純熟；三、社群運作結束後，教師給予逆向式課程設計正向的評價，但在教學實踐上仍有挑戰與困難。逆向式的課程設計有利於化解教師對於素養導向在知識概念與教學行動經驗間的衝突，在教師社群共備之下，持續進行專業教學對話與反思，成為素養導向體育教師增能培力之新策略。 The core competencies that 12-year Compulsory Education aims to develop are the basis of the curriculum development for each subject. Competence-based Physical Education（CBPE）curriculum, however, has not yet been popularized and implemented. The purpose of this study was to examine the backward design, and structure of the physical education unit intended to enhance physical education teachers' understanding and practical application of competency-oriented curriculum design. Five secondary school physical education teachers and one physical education teacher education professor was selected for this study, and four learning communities were organized. Data were collected through semi-structured interviews, participant observation, continuous comparison, and inductive analysis. Results were as follows: 1. In the initial community, teachers identified a contradiction between teaching and assessment, although assessments still emphasized skill acquisition; 2. During the community operation, teachers worked towards aligning the curriculum with learning objectives, assessment methods, and learning content, aiming to address the tension between "field teaching experience" and "inquiry learning"; however, they were not yet familiar with the CBPE assessment concept; 3. After the community operation, teachers provided positive feedback on the backward design approach, but encountered challenges and difficulties in implementing it during their teaching practice. Through the co-planning mechanism of teacher learning communities, which encourages dialogue and reflection in Physical Education classes, becoming a competence-based physical education teacher becomes a new strategy for enhancing abilities and training.